Reversible Causes of Cognitive Decline in Young Patients: A Narrative Review - Dobrovolskiy , D. (Journal of Education, Health and Sport, 2026)
Young-onset cognitive decline represents a major diagnostic challenge because, unlike age-related neurodegenerative dementias, a considerable proportion of cases are potentially reversible if recognized and treated promptly. This narrative review aimed to summarize current evidence regarding the etiology, pathogenesis, diagnostic approaches, and treatment strategies for reversible causes of cognitive decline in young patients. A literature search was conducted in PubMed, Scopus, Web of Science, and Google Scholar using keywords related to reversible dementia, young-onset cognitive impairment, metabolic encephalopathy, autoimmune encephalitis, and treatable causes of dementia. Original studies, systematic reviews, meta-analyses, and clinical guidelines published in English within the last 10 years were analyzed. The review demonstrated that metabolic and deficiency-related disorders, including vitamin B₁₂, folate, and thiamine deficiency, are among the most frequent reversible causes of cognitive impairment in younger individuals. Infectious conditions such as neurosyphilis, HIV-associated neurocognitive disorder, Lyme neuroborreliosis, viral encephalitis, and tuberculous meningitis may mimic dementia but often respond to etiological therapy. Autoimmune encephalitis, toxic exposures, medication-induced cognitive dysfunction, structural brain abnormalities, and psychiatric disorders, particularly depression-related pseudodementia, also play an important role. The diagnostic process should include detailed clinical assessment, laboratory screening, neuroimaging, and cerebrospinal fluid analysis when indicated. A multidisciplinary approach involving neurologists, psychiatrists, endocrinologists, infectious disease specialists, and other healthcare professionals is essential for timely diagnosis and effective treatment. Early identification of reversible causes of cognitive decline significantly improves prognosis and may result in substantial or complete restoration of cognitive function in young patients.